The Effects of Shopping Orientations on Online Purchase Intention in Malaysia - Zhu, Jia (2014)
There are about 17.7 million internet users in Malaysia which accounts for 60.7% of the total Malaysian population. Among the e-commerce, online shopping is a potential and growing industry in almost every nation includes Malaysia. However, Malaysians are relatively reluctant to shop online which compared to other countries. Moreover, there is quite limit research about the effect of shopping orientations on the consumer online purchase intention has been done by other researcher in Malaysia. Based on these, this research aims to reconfirm the reasons why some Malaysian internet users refuse to purchase products/services online. Also it seeks to assess the effect of shopping orientations on online purchase intention in Malaysia. Besides, it aims to assess which shopping orientation has the greatest impact on online purchase intention in Malaysia. Results of findings show that security concern and privacy concern are main concerns for Malaysian internet users refuse to shop online. All the five shopping orientations which are impulse purchase orientation, quality orientation, brand orientation, shopping enjoyment orientation, and convenience orientation are positively related online purchase intention. In addition, convenience orientation is found that has the strongest influence on consumer online purchase intention in Malaysia.